Full inhibition of enzymatic browning in the presence of thiol-functionalised silica nanomaterial. (15th February 2018) - Muñoz-Pina, Sara; Ros-Lis, José V.; Argüelles, Ángel; Coll, Carmen; Martínez-Máñez, Ramón; Andrés, Ana
Highlights: Use of nanomaterials to inhibit polyphenol oxidase has rarely been tested before. Mesoporous silica materials, non-functionalised or functionalised with thiol groups, were tested. All the materials inhibit enzymatic browning and thiol enhances the effect. Thiol-containing bimodal mesoporus material with big pore size offers the greatest inactivation, even in real systems. Abstract: Darkening processed fruits and vegetables is caused mainly by enzymatic browning through polyphenol oxidase (PPO) action. Accordingly, we explored the potential of four silica-based materials (MCM-41 nanometric size, MCM-41 micrometric size, UVM-7 and aerosil), non-functionalised and functionalised with thiol groups, to inhibit PPO activity in the model system and apple juice. All materials showed relevant performance when immobilising and inhibiting PPO in model systems, and support topology is a main factor for enzyme immobilisation and inhibition. Thiol-containing silica UVM7-SH showed the greatest inactivation, and similar browning values to those obtained by acidification. The enzyme's kinetic parameters in the presence of UVM-7-SH suggested non-competitive inhibition, which indicated that the material interacted with the enzyme, but beyond the active centre. In real systems, UVM-7-SH completely inhibited enzymatic browning in apple juice (cv. Granny Smith and cv. Golden Delicious) up to 9 days after 5 min of contact.